CHARACTERISTICS OF CHRISTIAN TATAR (KRYASHENS) DIALECTS - Ercan ALKAYA; Zoya KİRİLLOVA (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2018)
This study eloborates the characteristics of the dialect of Christian Tatars, a special group of Tatar people. Christian Tatars are classified under five categories regarding the language features and the regions they live. In this study, each of these groups are mentioned briefly. In addition, common and different linguistic features of Christian Tatar dialects with standart language and other Tatar dialects are presented. Escpecially, phonetic features such as sound correspondences, paromasis, dissimilation, epenthesis and elision, preserving the arkhaic Turkish phonetic chracteristics are emphasized. The characteristic vocabularies are clearly seen in religious-related onomathesias acquired through Christianity, tangible and intangible cultural words. Besides, the preserved archaic Turkish words and Persian, Russian, Chuvash, Udmurtian, Mari origin loan words are also significant. In thish study, the common morphological aspects of Christian Tatar dialect with Tatar standart language and Middle (Kazan), Western (Misher) dialects are also mentioned.